Effect of microstructural features on the failure behavior of hybrid laser welded AA7020. Issue 9 (10th May 2018) - Hu, Y.N.; Wu, S.C.; Song, Z.; Fu, Y.N.; Yuan, Q.X.; Zhang, L.L.
Abstract: Detailed investigations of microstructural feature, mechanical property, fatigue strength, and damage mechanism were conducted on hybrid laser welded 7020‐T651 aluminum alloys used into high‐speed railway vehicles. The results show that the hybrid laser welding process can induce significant changes of microstructures and alloying elements, together with numerous gas pores. Such local modifications degrade the fatigue performance. The tensile strength of welded joints was approximately 74% with respect to the base metal, thus satisfying the design standard. The fatigue property was determined in the low and high cycle regimes. It was found that the fatigue strength of welded joints was fairly inferior to that of the base metal, but far higher than the IIW recommended value. Furthermore, welding defects were well believed to contribute to the shorter fatigue life. The small fatigue crack growth presented highly discontinuous and inhomogeneous due to microstructure and porosity. By contrast, the crack stable growth stage was less sensitive to microstructural features of hybrid welded joints.